2011
DOI: 10.1038/leu.2011.349
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte globulin for acute-graft-versus-host-disease prophylaxis in patients undergoing allogeneic hematopoietic cell transplantation: a systematic review

Abstract: Graft-versus-host-disease (GVHD) is a major complication associated with allogeneic hematopoietic cell transplantation (allo-HCT). Antithymocyte globulin (ATG) is recommended for GVHD prophylaxis following allo-HCT, however, evidence on efficacy of ATG is conflicting. Accordingly, we undertook a systematic review. All phase III randomized controlled trials (RCTs) comparing ATG versus control for prevention of GVHD in patients undergoing allo-HCT were eligible. Medline and Cochrane databases were searched. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
2
39
0
1
Order By: Relevance
“…The incidence of cGVHD was only 33.3% in the FBCA conditioning regimen group, and most of the cGVHD in this group were limited, whereas the incidence of the chronic GVHD in the FBC conditioning regime group was as high as 83.3% and 69.4% of these were extensive cGVHD. These results are consistent with those reported by Bacigalupo [26] and systematic reviewed by Kumar [27]. The statistical analysis also indicated that an addition of ATG-F to the conditioning regimen could prolong survival.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The incidence of cGVHD was only 33.3% in the FBCA conditioning regimen group, and most of the cGVHD in this group were limited, whereas the incidence of the chronic GVHD in the FBC conditioning regime group was as high as 83.3% and 69.4% of these were extensive cGVHD. These results are consistent with those reported by Bacigalupo [26] and systematic reviewed by Kumar [27]. The statistical analysis also indicated that an addition of ATG-F to the conditioning regimen could prolong survival.…”
Section: Discussionsupporting
confidence: 82%
“…The 2-year cumulative incidence of extensive cGVHD was 12.2% versus 42.6% (P = 0.0001). It has been known that the addition of ATG to conditioning regimens can not only reduce the incidences of aGVHD and cGVHD significantly but also facilitate engraftment in allo-SCT [13][14][15]. Despite promising result in GVHD prevention and graft facilitation, ATG use is greatly limited by multiple side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Use of ATG has been associated with reduced incidence and severity of acute and chronic GVHD. 29,30 Patients who received FB4 achieved an earlier ANC engraftment (15 vs 17 days, P o0.0001) despite the fact that PBSC was more commonly used in allografted recipients conditioned with FB2 (Table 1). Patients who received FB4 had a higher incidence of SOS/VOD (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6 As peripheral blood stem cells have become more commonly used as stem cell source, strategies to prevent chronic GVHD without increasing the risk of relapse are needed. 1 ATG has been widely used in HLA-matched and -mismatched unrelated stem cell transplantation in randomized and nonrandomized trials [7][8][9][10]16,17 showing a reduction in severe acute GVHD and more strikingly a reduction in chronic GVHD. Our previous experience using ATG-Fresenius as part of the conditioning in the setting of HLA-identical bone marrow transplantation has shown a significant reduction in acute and chronic GVHD without an obvious risk of relapse.…”
Section: Discussionmentioning
confidence: 99%